THE STATISTICAL AND CONSTRUCTIVE DECISION OF JUNCTION POINTS OF PANEL OBJECTS - Luchko, Y. Y.; Tsibelenko, P. P.; Lembak, M. V. (Science and Transport Progress, 2010)
The conducted experimental researches of «dry» joints with screw-bolt connection have shown that these joints had considerably larger deformations than the joints with the concrete filling. From the viewpoint of greater deformativeness, the «dry» joints under critical loadings are more reliable than the concrete-filled joints.